1991
DOI: 10.1111/j.1530-0277.1991.tb05203.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Characterization of Brain Neurotensin Receptor Subtypes in LS and SS Mice

Abstract: Neurotensin (NT) receptor subtypes were investigated in nine brain regions from long sleep (LS) and short sleep (SS) mice that were selectively bred for differences in sensitivity to ethanol. Differences in NT receptor densities may mediate, in part, genetically selected differences in ethanol sensitivity between the two lines of mice. The use of [3H] NT at concentrations from 0.02 to 20 nM yielded biphasic binding isotherms as revealed by Scatchard analysis. Membranes from LS ventral midbrain yielded dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We previously reported that NTS1 receptor densities were higher in several brain regions of SS mice selectively bred for low sensitivity to ethanol-induced LORR, compared with LS mice that were selectively bred for high sensitivity to LORR; that is, densities of NTS1 were higher in the ventral midbrain and frontal cortex of SS mice but were not different in striatum (Campbell et al, 1991). This observation is not consistent with a model in which NTS1 density was coselected with LORR, as suggested by the positive correlations between striatal NTS1 density and hypnotic sensitivity to ethanol (positive with LORR and QTLs were mapped with the use of the MAPMAKER/QTL software package.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We previously reported that NTS1 receptor densities were higher in several brain regions of SS mice selectively bred for low sensitivity to ethanol-induced LORR, compared with LS mice that were selectively bred for high sensitivity to LORR; that is, densities of NTS1 were higher in the ventral midbrain and frontal cortex of SS mice but were not different in striatum (Campbell et al, 1991). This observation is not consistent with a model in which NTS1 density was coselected with LORR, as suggested by the positive correlations between striatal NTS1 density and hypnotic sensitivity to ethanol (positive with LORR and QTLs were mapped with the use of the MAPMAKER/QTL software package.…”
Section: Discussionmentioning
confidence: 91%
“…Studies of neurotensin receptors from rat and mouse brain revealed biphasic binding isotherms best described by two independent binding sites: high-affinity (NTS1) and low-affinity (nts2; Campbell et al, 1991;Mazella et al, 1989). The H 1 histamine antagonist, levocabastine, has been shown to selectively inhibit binding of NT to nts2 (Campbell et al, 1991;Mazella et al, 1989), which provides a valuable tool to distinguish between NTS1 and nts2.…”
Section: E Vidence Indicates a Heritable Component Tomentioning
confidence: 99%
See 2 more Smart Citations
“…NT markedly enhanced ethanol sensitivity, assessed by ethanol-induced anesthesia and increased sleep duration, two-fold in rats [159], and up to three-fold in mice, in a dose-dependent manner [160]. The role of the neurotensinergic system in ethanol consumption was launched and consolidated by Gene Erwin and his colleagues [161][162][163][164][165][166][167][168][169][170][171][172]. Firstly, they showed that this NT-induced enhancement of ethanol sensitivity was different in SS compared to LS mice.…”
Section: Ethanol Consumptionmentioning
confidence: 99%